2001
DOI: 10.1007/pl00011739
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of jejunal pouch added to Roux-en-Y reconstruction after total gastrectomy

Abstract: We conclude that, 2 years after total gastrectomy, the pouch reconstruction had alleviated postgastrectomy symptoms to a greater extent than simple Roux-en-Y reconstruction, but the effectiveness could be improved. The long-term effects of pouch reconstruction should be examined more precisely with an adequate and valid scoring system for determining quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…Bozzetti et al [28] reported that there were no differences in BW and eating habits between these 2 groups but that after JPRY-T, there were less gastrointestinal symptoms; although they concluded that there was no substantive benefit of pouch reconstruction, we classified their results as ‘positive’ according to our definition. The remaining 4 studies showed a benefit with JPRY-T in terms of eating capacity, food intake, BW, nutrition and symptoms [29,30,31,32]. When considered together, these 9 studies suggest that the postoperative results of JPRY-T are generally more favorable than those of RY-T.…”
Section: Resultsmentioning
confidence: 99%
“…Bozzetti et al [28] reported that there were no differences in BW and eating habits between these 2 groups but that after JPRY-T, there were less gastrointestinal symptoms; although they concluded that there was no substantive benefit of pouch reconstruction, we classified their results as ‘positive’ according to our definition. The remaining 4 studies showed a benefit with JPRY-T in terms of eating capacity, food intake, BW, nutrition and symptoms [29,30,31,32]. When considered together, these 9 studies suggest that the postoperative results of JPRY-T are generally more favorable than those of RY-T.…”
Section: Resultsmentioning
confidence: 99%
“…food stasis in the jejunal J pouch) and there are no advantages. 18,25 Ikeda et al showed that an adequate size is considered to be 15-20 cm in length, as determined scintigraphically. 25 In Japan, Tanaka et al reported that bending of a 20-cm jejunal pouch inhibits reservoir function, and recommended a 15-cm reconstruction with a double tract procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Miyoshi et al suggested that pouch reconstruction has the advantage of leading to a more favourable eating capacity to prevent microgastria and fewer postoperative symptoms, including loss of appetite, ARE and EDS. 18 There are some reports that pouch reconstruction can allow large meals that frequently reach preoperative levels. [22][23][24] However, an important problem in pouch reconstruction is how to determine an adequate size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of body weight is a common sequela of gastrectomy; however, there has been no consensual explanation for the impact of gastrectomy on nutritional status (Miyoshi et al, 2001;Katai et al, 2003). Complex mechanisms seem to be involved, including abnormal transit and diarrhea (Takase et al, 2003), dumping syndrome (Schölmerich, 2004), reduced food intake because of early satiety and loss of appetite (Liedman et al, 2001;Bergh et al, 2003), and alteration of endocrine status, such as reduced ghrelin release (Date et al, 2000;Hosoda et al, 2006) or increased satiety mediators such as cholecystokinin (Bergh et al, 2003), PYY 3À36 (Stratis et al, 2006;Borg et al, 2007) or glucagon-like peptide-1 (Borg et al, 2007).…”
Section: Introductionmentioning
confidence: 99%